Simulation sensitivities of the major weather regimes of the Southeast Asia region - Chainarong Raktham (2018)
© 2014, The Author(s). This study evaluates the Weather Research and Forecasting model’s ability to simulate major weather phenomena [dry conditions, tropical cyclones (TCs) and monsoonal flow] over East and Southeast Asia. Sensitivity tests comprising different cumulus (Kain–Fritsch and Betts–Miller–Janjic) and microphysics (Purdue Lin, WSM3, WSM6 and Thompson) are used together with different placement of lateral boundaries to understand and identify suitable model configuration for weather and climate simulations over the Asia region. All simulations are driven with reanalysis data and use a nominal grid spacing of 36 km, with 51 levels in the vertical. The dry season showed little sensitivity to any configuration choices, while the TC case shows high sensitivity to the cumulus scheme and low sensitivity to the microphysical scheme. Monsoon simulations displayed significant sensitivity to the placement of the lateral boundaries.